Roundtable discussion on food security in Nigeria with US ambassador to Nigeria - Onilogbo, Omobolanle (CGIAR System Organization, 2022)
On August 3, 2022, the U.S. Ambassador to Nigeria, Mary Beth Leonard, invited food security experts, including Kwaw Andam, CGIAR Research Initiative on National Policies and Strategies (NPS) Nigeria Country Lead and Country Program Leader of IFPRI Nigeria, to a roundtable discussion on the food situation in Nigeria. Other participants included representatives from the United States Agency for International Development (USAID)/Nigeria, United Nations Children’s Fund (UNICEF), World Food Programme (WFP), the Nigerian Institute of Social and Economic Research (NISER), the Nigerian Agribusiness Group (NABG), and a Mandela Washington Fellow (MWF).